Pendampingan Kompetensi Failure Mode Effect Analysis (FMEA) Sebagai Upaya Deteksi Dini Permasalahan Pelayanan Kesehatan di RSUD Sadikin Kota Pariaman - Adila Kasni Astiena; Rizanda Machmud; Rima Semiarty; Yuniar Lestari; Firdawati; Husna Yetti; Rosfita Rasyid; Ida Rahmah Burhan; Hardisman; Abdiana; Zurayya Fadilla; Nelmi Silvia; Anung Respati; Dyanti Oktalina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Hospitals are not systematically designed to detect service errors as in non-healthcare products, thus increasing risks to patient safety. RSUD Sadikin in Pariaman City, which has been operating for only seven years, has not yet established mechanisms or training to detect service errors. This community service activity aimed to enhance managerial competence in managing the risk of healthcare service errors through the application of Failure Mode and Effect Analysis (FMEA). The activity was conducted in the form of a workshop involving 30 participants from top, middle, and lower management levels in Oktober-November 2025 at Sadikin Hospital. FMEA competence was assessed before and after the workshop using a paired t-test. The results showed that the mean pre-test score was 70.67 (SD±17.604) and the post-test score was 84.67 (SD±14.794), with an improvement of 14.00 points (SD±14.004), which was statistically significant (p=0.000). These findings indicate that the FMEA workshop effectively improved participants’ managerial competence in early detection and mitigation of service risks. Follow-up mentoring is recommended to evaluate the sustainability of training effects at 3, 6, and 9 months after the activity.